Stand in surgeon’s shoes: virtual reality cross-training to enhance teamwork in surgery - Killeen, Benjamin D.; Zhang, Han; Wang, Liam J.; Liu, Zixuan; Kleinbeck, Constantin; Rosen, Michael; Taylor, Russell H.; Osgood, Greg; Unberath, Mathias (International Journal of Computer Assisted Radiology and Surgery, 2024)
Purpose: Teamwork in surgery depends on a shared mental model of success, i.e., a common understanding of objectives in the operating room. A shared model leads to increased engagement among team members and is associated with fewer complications and overall better outcomes for patients. However, clinical training typically focuses on role-specific skills, leaving individuals to acquire a shared model indirectly through on-the-job experience. Methods: We investigate whether virtual reality (VR) cross-training, i.elet@tokeneonedotexposure to other roles, can enhance a shared mental model for non-surgeons more directly. Our study focuses on X-ray guided pelvic trauma surgery, a procedure where successful communication depends on the shared model between the surgeon and a C-arm technologist. We present a VR environment supporting both roles and evaluate a cross-training curriculum in which non-surgeons swap roles with the surgeon. Results: Exposure to the surgical task resulted in higher engagement with the C-arm technologist role in VR, as measured by the mental demand and effort expended by participants (p<0.001). It also has a significant effect on non-surgeon’s mental model of the overall task; novice participants’ estimation of the mental demand and effort required for the surgeon’s task increases after training, while their perception of overall performance decreases (p<0.05), indicating a gap in understanding based solely on observation. This phenomenon was also present for a professional C-arm technologist. Conclusion: Until now, VR applications for clinical training have focused on virtualizing existing curricula. We demonstrate how novel approaches which are not possible outside of a virtual environment, such as role swapping, may enhance the shared mental model of surgical teams by contextualizing each individual’s role within the overall task in a time- and cost-efficient manner. As workflows grow increasingly sophisticated, we see VR curricula as being able to directly foster a shared model for success, ultimately benefiting patient outcomes through more effective teamwork in surgery.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Computer-assisted interventions; Image-guided; Surgical training; X-ray